Utilization of Spin The Wheel to Increase Student Participation in the Learning Process: Penggunaan Spin the Wheel untuk Meningkatkan Partisipasi Peserta Didik dalam Proses Pembelajaran - Prasetya, Kadek Dipa (B-CRETA Publisher (CV. Borneo Citra Kreatama), 2025)
In an effective learning process, active participation is required from all parties involved, both teachers and students. Active participation can be in the form of speaking, listening, reading and writing. This participation must be accompanied by learning media used to make it easier for teachers to convey the meaning of the material being taught. The purpose of this research is to see how Spin The Wheel media can increase student's participation in the learning process so that the process does not only take place in one direction.